2007
DOI: 10.1093/carcin/bgm213
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositol phosphatase SHIP2 promotes cancer development and metastasis coupled with alterations in EGF receptor turnover

Abstract: Phosphoinositol phosphatases are important regulators of signaling pathways relevant to both diabetes and cancer. A 3'-phosphoinositol phosphatase, phosphatase homologous to tensin (PTEN), is both a tumor suppressor and a negative regulator of insulin action. A 5'-phosphoinositol phosphatase, SH2-containing 5'-inositol phosphatase (SHIP2), regulates insulin signaling and its genetic knockout prevents high-fat diet-induced obesity in mice. SHIP2 also regulates cytoskeleton remodeling and receptor endocytosis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
79
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 49 publications
9
79
1
1
Order By: Relevance
“…PtdIns(3,4)P 2 was demonstrated to have a higher affinity for Akt than PtdIns(3,4,5)P 3 , (14), and in accordance with this finding, several studies have shown that reduction of SHIP2 activity may result in decreased, rather then increased, Akt activity, leading to reduced proliferation and enhanced cell death (15,24). SHIP2 overexpression has been described in primary breast cancer, and SHIP2 is required for the prosurvival signal initiated by epidermal growth factor receptor in this tumor type (25). We now describe three novel pan-SHIP inhibitors, which were able to effectively kill two breast cancer cell lines in addition to three MM cell lines.…”
Section: Discussionmentioning
confidence: 56%
“…PtdIns(3,4)P 2 was demonstrated to have a higher affinity for Akt than PtdIns(3,4,5)P 3 , (14), and in accordance with this finding, several studies have shown that reduction of SHIP2 activity may result in decreased, rather then increased, Akt activity, leading to reduced proliferation and enhanced cell death (15,24). SHIP2 overexpression has been described in primary breast cancer, and SHIP2 is required for the prosurvival signal initiated by epidermal growth factor receptor in this tumor type (25). We now describe three novel pan-SHIP inhibitors, which were able to effectively kill two breast cancer cell lines in addition to three MM cell lines.…”
Section: Discussionmentioning
confidence: 56%
“…Reports in the literature reveal that the function of SHIP2 as a pro-or anti-oncogene is not clear and very much depends on the cellular model Prasad et al, 2008a;Taylor et al, 2000). In breast cancer cells, where it has been mostly studied, SHIP2 participates in the mechanism of invadopodium maturation by producing the key lipid PI(3,4)P2 (Sharma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These two proteins, along with STAM, CBL, and the 5Ј-phosphoinositol phosphatase SHIP2 were previously identified as Y phosphorylated and part of the EGFR network (46). SHIP2 is linked to RTK signaling through its SH2 domain, is an effector of EGFR endocytosis (47), and considered a drug target in breast cancer, where its expression was linked to EGFR inhibitor sensitivity in MDA-231 cells (48). Epsin-4 interacts with clathrin and the AP-2 complex (including AP2B1 identified herein).…”
Section: Discussionmentioning
confidence: 99%